2005
DOI: 10.1007/s00420-004-0583-5
|View full text |Cite
|
Sign up to set email alerts
|

Work-related accidents and occupational diseases in veterinarians and their staff

Abstract: Prevention strategies for veterinarians should focus on accidents caused by animals. The prevention of occupational diseases should focus on skin diseases, respiratory disease, and infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
97
0
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(111 citation statements)
references
References 26 publications
8
97
0
6
Order By: Relevance
“…[9][10][11][12] It is known that 868 of 1,415 (61%) known human pathogens and 132 of 175 (75%) emerging diseases that affect humans are zoonotic. 13 There are > 50 zoonotic diseases of importance in the United States (Appendix 1).…”
Section: B Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…[9][10][11][12] It is known that 868 of 1,415 (61%) known human pathogens and 132 of 175 (75%) emerging diseases that affect humans are zoonotic. 13 There are > 50 zoonotic diseases of importance in the United States (Appendix 1).…”
Section: B Backgroundmentioning
confidence: 99%
“…During their careers, approximately two-thirds of veterinarians report a major animal-related injury that resulted in lost work time or hospitalization. 9,10,[60][61][62] The most common occupational injuries among veterinary personnel include animal bites and scratches, kick and crush injuries, and needlesticks. [63][64][65][66][67][68][69][70][71][72] The VSP described in this document should be used consistently by veterinary personnel-regardless of the clinical condition or the presumed diagnosis of animals in their care-whenever personnel may be exposed to potentially infectious materials including feces, blood, body fluids, vomitus, exudates, work surfaces contaminated with these items, and nonintact skin.…”
Section: Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Being bitten, being scratched, other traumas, injuries, muscle-skeletal system diseases, car accidents, and having zoonosis diseases are the leading ones [13,[26][27][28][29] . Data from Australia [13] , New Zealand [25] and Germany studies [14,30] were similar to stressors reported from our study group.…”
Section: Discussionmentioning
confidence: 99%
“…CU or PCD from animal proteins is often accompanied by respiratory symptoms, and the respiratory symptoms may precede skin symptoms by years (Aoyama et al 1992;Nienhaus et al 2005;Spiewak et al 2000;Spiewak 2004;Barbuzza et al 2009;Helaskoski et al 2017;Muzembo et al 2014). Skin tests for immediate allergy (e.g., SPT) or specific IgE have been positive with animal dander, hair, amniotic fluid, serum, blood, organs, milk, and saliva (Rudzki 1975;Prahl and Roed-Petersen 1979;Hjorth and Roed-Petersen 1980;Slovak and Hill 1981;Degreff et al 1984;Agrup and Sjöstedt 1985;Falk et al 1985;Kalveram et al 1986;Weissenbach et al 1988;Karches and Fuchs 1993;Buckle and Devos 2007;Valsecchi et al 2003).…”
Section: Diagnosis Of Animal Allergymentioning
confidence: 99%